Efficacy and safety of 5% glycolic acid‐based Gel essence in the treatment of mild to moderate acne. (28th February 2022) - Chen, Linjiao; Lu, Lingling; Tu, Shaozhong; Zhang, Tao; Du, Xianni; Chen, Lifen; Zhang, Milin; Li, Lihao; Lin, Huaner
Abstract: The efficacy and safety of commercial low‐concentration glycolic acid products on acne were evaluated by recruiting volunteers accompanying mild to moderate acne of different ages and genders, which is a clinical practice for acne. We recruited a total of 30 volunteers according to the inclusion criteria, conducting clinical evaluation and skin physiological index testing, VISIA skin analysis, distributing products, and informing the trial method. Clinical testing and assessment will be carried out in weeks 0, 1, 2, and 4. 27 acne volunteers finished the entire trial. After 4 weeks of using low‐concentration glycolic acid products, most subjects experienced a significant improvement in their skin lesions and the GAGS score. At the same time, the VISIA test showed that the subjects had an obvious amelioration in facial porphyrins, which was statistically significant, and there was a slight improvement in residual spots and erythema. The skin physiological indexes showed that the skin hydration value increased from 236.2 ± 98.05 to 278.2 ± 90.26 after 14 days. At the end of the test, the skin hydration value dropped to 234.6 ± 81.88. Regarding the melanin and erythema, the value decreased in the 4th week significantly. Repeated use of 5% low‐concentration glycolic acid improves the appearance and chromaticity of the treatment site. It increases the brightness L* and reduces the redness a*. This study shows that low concentrations of glycolic acids have a good effect on the treatment of mild to moderate acne. It may pay the way to carry out further large‐scale clinical research.